Green Banking for Sustainable Development - Fakhri Fuad Murshudli (Foresight and STI Governance)
The ever-increasing threat of global climate change, environmental pollution, and the destructive impact of human activities highlight the need for more detailed research into tools to increase a country’s environmental sustainability. In addition, it promotes the search for additional sources of funding for these activities. For developing countries, one of the main sources of environmentally sustainable development is international bank financing. Therefore, this study aims to analyze how international green banking affects the environmental sustainability of developing countries. For this purpose, the data series were compiled for the period of 2010 to 2020. The annual data for panel regression analysis are retrieved from the OECD and World Bank Open Data. The identified effects can be useful for government officials in terms of determining the benefits of using international green banking for gaining environmental sustainability.